Coda /s/ weakening in Santiago and Concepción, Chile - Rogers, Brandon M. A.; Bolyanatz, Mariška (Boletín de Filología, 2023)
The majority of studies regarding coda /s/ in Chilean Spanish have asserted that the [h] allophone is the most frequently used, in addition to being the allophone that carries the most social prestige. On the basis of acoustic analysis in Praat of 90 sociolinguistic interviews (30 from Concepción, 60 from Santiago), our statistical analysis demonstrated that not only is [∅] the most frequently used allophone of coda /s/ (among all speakers, regardless of age), and we also found a diatopic uniformity between the cities of Concepción and Santiago. Taken together, these findings indicate that [∅] has been the most frequently used allophone in these cities for some time. Additionally, we present evidence for some patterns that suggest a possible change in progress led by younger speakers who favor the use of a shortened allophone of [s] particularly before /t̪/. Our results suggest that future studies should rely on acoustic analysis of a more representative socioeconomic sample in order to account for the range of phonetic variation present in Chilean Spanish.